Montelukast As An Add On Therapy In Asthma As Compared To Its Use In Asthma Associated With Concomitant Rhinitis Symptoms - Sultan, kassim M. (Journal of the Faculty of Medicine Baghdad, 2011)
Back ground: The use of Montelukast in mild and moderate asthma has been studied ,allergic rhinitis or rhinitis and asthma are strongly inter related, Montelukast has been used in both conditions, whether treating rhinitis will improve asthma control ,a point which has been stressed recently.Objectives: To evaluate the effect of Montelukast in mild and moderate asthma according to Global INitiative For Asthma guidelines ( GINA),and to compare its use in asthma alone and in asthma which is associated with persistant rhinitis symptoms.Patients and methods: Seventy patients who fulfill the criteria of mild and moderate asthma according to Global INitiative For Asthma guidelines had been recruited from the consultation clinic of the respiratory diseases in Baghdad Teaching Hospital from the 111st.July 2009 to 31st. December 2010,patients were divided in to 2 groups : Group – 1 patients with asthma only which was subdivided into 2 sub groups: 1-a on salbutamol inhaler on need and 1-b on beclomethasone inhaler 800Mgm/day in addition to salbutamol inhaler on need. Group- 2 patients with asthma and rhinitis which was sub divided in to subgroups: 2-a on salbutamol inhaler on need and 2-b on beclomethasone 800Mgmlday in addition to salbutamol inhaler on need.Evaluation of day and night time symptoms, records of rhinitis symptoms and measurement of FEV1(Forced Expiratory Volume in 1st. second) and FEF 25-75%(Forced Expiratory Flow)were done to all patients . Montelukast 10 mg/ day was given to all patients for 4 weeks,and reevaluation for day , night time symptoms , rhinitis symptoms and measurement of FEV1 and FEF 25-75% were done . Results: There was a significant statiscal improvement in day , night time symptoms , FEV1 , FEF 25-75% and rhinitis symptoms after Montelukast treatment than before treatment ( p value < 0.05), Montelukast use in asthma alone as compared to its use in asthma which was associated with rhinitis did not show a significant statiscal improvement in outcome response in day,night symptoms and in percentage of change in FEV1 and FEF25-75% (p value>0.05) .Conclusion: Montelukast improved day , night time symptoms , FEV1 , FEF 25-75% in mild and moderate asthma ,it also improved rhinitis symptoms but Montelukast use in asthma alone ascompared to its use in asthma which was associated with rhinitis did not show a significant statiscal imrovement in asthma control regarding day,night time symptoms,FEV1 and FEF25-75% values .